Influence of family and academic satisfaction on life satisfaction among Peruvian university students in the times of COVID-19: The mediating role of self-esteem - Carranza Esteban, Renzo Felipe; Mamani-Benito, Oscar; Castillo-Blanco, Ronald; Lingan, Susana K.; Cabrera-Orosco, Isabel (Frontiers in Education, 2022)
Objective To examine the effect of family and academic satisfaction on the self-esteem and life satisfaction among Peruvian university students. Method Of the 1,182 Peruvian university students who participated, 364 were male; and 818 were female; and ranged from 17 to 39 years of age (mean = 20.67, SD = 4.4). The family satisfaction scale (FSS), the Escala breve de satisfacción con los estudios (EBSE; Brief Academic Satisfaction Scale in Spanish), Rosenberg’s self-esteem scale (RSES), and the satisfaction with life scale (SWLS) were used to perform the assessments. Results The study model showed an adequate fit (χ2 19.5, p < 0.001, CFI = 0.977, RMSEA = 0.057), confirming the association between family satisfaction and life satisfaction (β = 0.26, p < 0.001) and self-esteem (β = 0.35, p < 0.001), and the correlation between academic satisfaction and self-esteem (β = 0.35, p < 0.001) and life satisfaction (β = 0.23, p < 0.001). The model accounted for 42% of life satisfaction. Conclusion Family satisfaction and academic satisfaction affect self-esteem and life satisfaction.